Experimental and phenomenological study of the effects of adding shredded tire chips on geotechnical properties of peat. Issue 4 (4th July 2018) - Saberian, Mohammad; Mehrinejad Khotbehsara, Mojdeh; Jahandari, Soheil; Vali, Ramin; Li, Jie
Abstract : Due to the high values of organic and water contents, and other poor geotechnical properties of peats, it is essential to stabilise peat deposits. Moreover, in recent decades, accumulation of waste tires has caused myriad environmental problems all around the world. To tackle both issues, a reasonable remedy is to use scrap tires for stabilisation of peat soils. Since some of geotechnical properties of tire stabilised peats have been not reported yet, the aim of this study is to investigate the effects of adding different weight percentages of shredded tire chips (0, 5, 10, 15 and 20%) along with constant amount of sand (400 kg/m 3 ) on some of geotechnical properties of stabilised peat such as unconfined compressive strength (UCS), secant modulus ( E s ), failure strain ( ε f ), brittleness index ( I B ), deformability indexes ( I D ), resilient modulus ( M r ), bulk modulus ( K ), shear modulus ( G ), cohesion ( C ) and angle of internal friction ( φ ) using UCS and direct shear tests. Moreover, to chemically characterise sand and peat, X-ray fluorescence test was conducted. Based on the test results, there was an upward trend in E s, M r, K and G with some mild fluctuations due to the changes of bonds between peat and tire chips caused by the reduction in consistency and homogeneity of the stabilised peat; and overcoming the change by increasing the percentages of tire chips. Furthermore, from UCS test, the maximum values of UCS, E s, G, K and M r were observed in the specimen with 10% shredded tire chips at 405.41 kPa, 3.43 MPa, 1.44 MPa, 1.64 MPa and 119.07 MPa, respectively. Also, adding chips to the peat increased the ductile behaviour of the soil. Moreover, by increasing the tire chips, C and φ parameters increased significantly. From SEM test, it was observed that the stabilised peat was characterised by a rather well-structured matrix since the pore spaces were mostly filled by sand. Finally, based on the experimental results, a phenomenological model was used to develop equations for predicting the geotechnical properties with the percentages of shredded tires. The results showed that there was a good correlation between the measured parameters and those of the estimated ones given by the predicted equations. At last, the use of tire chips from scrap tires adds obvious environmental interest to this research.